2013
DOI: 10.1007/s11011-013-9446-7
|View full text |Cite
|
Sign up to set email alerts
|

Glia activation and its role in oxidative stress

Abstract: Glia activation and neuroinflamation are major factors implicated in the aetiology of most neurodegenerative diseases (NDDs). Several agents and toxins have been known to be capable of inducing glia activation an inflammatory response; most of which are active substances that can cause oxidative stress by inducing production of reactive oxygen species (ROS). Neurogenesis on the other hand involves metabolic and structural interaction between neurogenic and glia cells of the periventricular zone (PVZ); a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Proinflammatory signaling and glial activation plays a central role in brain damage in NDDs (Iadecola & Anrather, ; Ogundele et al, ). Proinflammatory signals are initiated in all phases, engaging both the innate and adaptive responses.…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory signaling and glial activation plays a central role in brain damage in NDDs (Iadecola & Anrather, ; Ogundele et al, ). Proinflammatory signals are initiated in all phases, engaging both the innate and adaptive responses.…”
Section: Pharmacologymentioning
confidence: 99%
“…Furthermore, mNCX blockade avoids mitochondrial Ca 2+ depletion and augments ATP synthesis and neuronal viability. On the other hand, OS induces glial activation by several mechanisms inducing the expression of RNS production enzyme iNOS and the release of cytokines (Ogundele et al, ). The interconnection of OS and neuroinflammation generates a vicious cycle, known as chronic neuroinflammation, that leads to extended neuronal damage.…”
Section: Introduction and Compound Designmentioning
confidence: 99%
“…At the systemic level, HPA axis dysfunction is the main mechanism to induce a LOAD phenotype by behavioral stress [88,89] . At the intercellular level, cerebrovascular dysfunction, Aβ accumulation [57,90] , glial activation [91][92][93] , and metal toxicity [11][12][13] are generally responsible for an abnormal microenvironment surrounding neurons, and contribute to their dysfunction.…”
Section: Effects Of Environmental Factors On Load At the Intracellulamentioning
confidence: 99%
“…the main mechanism to induce AD phenotype [42,88,89] . At the intercellular level, cerebrovascular dysfunction, Aβ accumulation [57,90] , glial activation [91][92][93]99] , and metal toxicity [11][12][13] are responsible for creating an abnormal microenvironment around neurons. At the intracellular level, the imbalance between the activities of tau-related kinases and phosphatases [29,94,95] , and abnormal epigenetic modifi cation, especially DNA methylation and histone acetylation [96][97][98] , are associated with neuronal dysfunction in LOAD.…”
Section: Hpa Axis Dysfunction At the Systemic Levelmentioning
confidence: 99%
“… 15 , 16 , 21 – 24 In addition, our previous findings of glia activation, neuronal degeneration and proliferation induced by differential oxidative stress has revealed that regional differences exists in stress response elicited in the brain; specifically across the plastic and non-plastic brain regions. 25 …”
Section: Introductionmentioning
confidence: 99%